Formation of territorial community as a subject of local development - Blazhivska, Mariana (Central European Public Administration Review, 2020)
The study contains an analysis of the essence of decentralization and its impacts on the creation of territorial communities. Scholarly views on the essence of the concept of 'territorial community' are presented and its features mentioned. The factors that determine the regional development of the territorial community as a subject of economic relations in the region have been identified. The legislative regulation of the process of creation and development of territorial communities is analysed and the shortcomings of the current situation are pointed out. The degree of decentralization over the period 2018-2020 is briefly analysed and a description of the methodology for assessing the viability of the created territorial communities is given. It is emphasised that the methodology of formation of affluent territorial communities is described in the 2015 Ukrainian legislation and approved by the resolution of 8 April No. 214 "The methodology of formation of affluent territorial communities". The calculated indicators are given on the example of the Stepanivska united territorial community and its prospects of development are estimated. Recommendations for improving the conditions of formation and development of territorial communities in the conditions of decentralization in Ukraine have been developed. The empirical methodology used in the study proved to be liquid and can be applied in practice to the formation of the territorial community as a subject of local development.
Keywords: administrative-territorial unit; decentralizacija; decentralization; local self-government; lokalna samouprava; teritorialne skupnosti; territorial community; Ukraine; Ukrajina; upravno-teritorialna enota